Tracheoinnominate Artery Fistula Formation in a Child with Long-Term Tracheostomy Dependence - Chauhan, Jigar C.; Hertzog, James H.; Viteri, Shirley; Slamon, Nicholas B. (Journal of Pediatric Intensive Care, 2019)
We report a fatal tracheoinnominate artery fistula (TIF) in a 13-year-old female patient with long-term tracheostomy tube dependence due to chronic respiratory failure. Thirteen years after placement of her tracheostomy tube, the patient experienced two separate episodes of sentinel bleeding prior to a fatal hemorrhagic event. Diagnostic evaluation after the sentinel events was mostly nonconclusive. This case highlights the risk of TIF in pediatric age group, even years after initial tracheostomy tube placement, and the need for a high index of suspicion for TIF when children present with unexplained tracheal bleeding.
Keywords: tracheoinnominate artery fistula; tracheostomy; sentinel bleed